„To” Magdaleny Tulli - Wiegandt, Ewa (My University, 2013)
The article analyses and interprets "Włoskie szpilki" [Italian High Heels] in the context of autobiographic writing, which is a new phenomenon in Tulli’s creative development. The analysis of autobiographical writing consists in a description of subject-construction. The construction is determined by combination of roles: the real author, the literary author, and the narrator-character. The style of the novel is characterized by the use of Holocaust topoi, and “March talk”, which leads the writer to the discovery that Polish post-war antisemitism castigates Jews for concealing their extraction. The aesthetic of postmemory, manifested in the novel, is interpreted as a transition from the modern rhetoric of inexpressibility and unutterableness, to the postmodern aesthetic of expression of what is absent.
„It” by Magdalena Tulli
Keywords: Magdalena Tulli; autobiographical writing; Holocaust; Polish antisemitism